Condition Red : Essays, Interviews, and Commentaries - Komunyakaa, Yusef (Book collections on Project MUSE., 2017)
"Condition Red collects writing by one of America's most gifted and revered poets, Yusef Komunyakaa. While themes from his earlier prose collection, Blue Notes, run through Condition Red, this volume expresses a greater sense of urgency about the human condition and the role of the artist. Condition Red includes his powerful letter to Poetry magazine, asserting that "we writers (artists) cannot forget that we are responsible for what we conjure and embrace through language, whether in essays, novels, plays, poems, or songs." Also included are essays and interviews on: coming home to Bogalusa, Louisiana; the influence of religion on black poetry; language and eroticism; the visual artist Floyd Tunson; and the poets Robert Hayden, Walt Whitman, Clarence Major, and Etheridge Knight."--